2021
DOI: 10.1039/d0dt04421k
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative degradation of toxic organic pollutants by water soluble nonheme iron(iv)-oxo complexes of polydentate nitrogen donor ligands

Abstract: The ability of four mononuclear non-heme iron(IV)-oxo complexes supported by nitrogen donor polydentate ligands in degrading organic pollutants has been investigated. The water soluble iron(II) complexes upon treatment with ceric...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 55 publications
0
3
0
Order By: Relevance
“…There are a handful of reports in the literature on the oxidative dehalogenation of halophenols by iron complexes, including defluorination and dechlorination processes [6b,10] . Thus, a series of bioinspired water‐soluble iron(IV)‐oxo oxidants were synthesized with nitrogen‐based tetradentate and pentadentate ligands and shown to act as potential catalysts in the oxidative detoxification of a wide range of halophenols [11] . Recently, we have reported a study on the oxidative dehalogenation of a series of mono‐, di‐ and trihalophenols by an iron(IV)‐oxo intermediate supported by the pentadentate 2PyN2Q ligand (2PyN2Q=1,1‐di(pyridin‐2yl)‐ N , N ‐bis(quinolin‐2‐ylmethyl)methanamine) in an acetonitrile solvent [12] .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are a handful of reports in the literature on the oxidative dehalogenation of halophenols by iron complexes, including defluorination and dechlorination processes [6b,10] . Thus, a series of bioinspired water‐soluble iron(IV)‐oxo oxidants were synthesized with nitrogen‐based tetradentate and pentadentate ligands and shown to act as potential catalysts in the oxidative detoxification of a wide range of halophenols [11] . Recently, we have reported a study on the oxidative dehalogenation of a series of mono‐, di‐ and trihalophenols by an iron(IV)‐oxo intermediate supported by the pentadentate 2PyN2Q ligand (2PyN2Q=1,1‐di(pyridin‐2yl)‐ N , N ‐bis(quinolin‐2‐ylmethyl)methanamine) in an acetonitrile solvent [12] .…”
Section: Introductionmentioning
confidence: 99%
“…[6b,10] Thus, a series of bioinspired water-soluble iron(IV)-oxo oxidants were synthesized with nitrogen-based tetradentate and pentadentate ligands and shown to act as potential catalysts in the oxidative detoxification of a wide range of halophenols. [11] Recently, we have reported a study on the oxidative dehalogenation of a series of mono-, di-and trihalophenols by an iron(IV)-oxo intermediate supported by the pentadentate 2PyN2Q ligand (2PyN2Q = 1,1-di(pyridin-2yl)-N,N-bis(quinolin-2-ylmethyl)methanamine) in an acetonitrile solvent. [12] These studies identified a rate-determining hydrogen atom abstraction from the phenolic OÀ H bond by the iron(IV)-oxo complex from the second-order rate constants.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Paine and co-workers synthesized a series of iron(IV)-oxo complexes supported by polydentate nitrogen-donor ligands which performed the oxidative degradation of halophenols in an aqueous medium. 49 It was observed that water plays a vital role in most of the processes used for the degradation of halophenols. However, all the intermediates might not be stable in aqueous medium.…”
Section: Introductionmentioning
confidence: 99%